Taste Neurons with a sense of odour. (Research'eu results magazine)
Taste and smell are sensory mechanisms that act as gate-keepers to ensure that only good, safe food is consumed. EU-funded researchers have provided novel insight into these mechanisms using Drosophila melanogaster as an insect model.